(untitled) (Journal of University of Babylon for Engineering Sciences, 2023)
The rapid development of mobile technologies such as 4G and 5G and wireless networks lead to more research to employ a new range of frequencies, along with the necessity of reducing size and power consumption, moreover, it focuses on flexible antennas that can be used in a wide range of applications. This research investigates antenna design with three feeding methods (microstrip line feed, proximity coupled feed, and aperture coupled feed) and finds out the best feeding method. In the proposed design, a Rogers RT/duroid™ 5880 is used as a substrate, and all of the proposed designs were simulated via computer simulation technology (CST) software simulations. The antenna is supposed to operate at frequencies of 6 and 28 GHz. As a radiative element, a rectangular copper patch is used, and the ground is made of copper. The antenna main parameters like gain, directivity, radiation efficiency and VSWR were investigated.